THE EFFECT OF JOB EMBEDDESS ON WORK PRODUCTIVITY THROUGH WORK ENGAGEMENT AT PT PERKEBUNAN NUSANTARA III - Susan Novrini; Syaifuddin Syaifuddin; Fajar Rezeki Ananda Lubis; Elly Romy (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
The decline in company performance and productivity has had many negative impacts that are detrimental to the company. Therefore, it is important to examine the effect of Job Embeddedness on Work Productivity through Work Engagement at PT Perkebunan Nusantara III. The type of research used by the researchers in this study is quantitative. The population in this study was the community, students, and alumni of PT Perkebunan Nusantara III employees. The study sample size was 456. The results showed that Job Embeddedness significantly influenced work engagement at PT Perkebunan Nusantara III. Job Embeddedness also significantly influenced work productivity at PT Perkebunan Nusantara III. Furthermore, work engagement also significantly influenced work productivity at PT Perkebunan Nusantara III. Finally, it was found that Job Embeddedness significantly influenced work productivity through work engagement at PT Perkebunan Nusantara III.